1999
DOI: 10.1017/s0031182098003485
|View full text |Cite
|
Sign up to set email alerts
|

Breeding systems in Echinococcus granulosus (Cestoda; Taeniidae): selfing or outcrossing?

Abstract: We used the PCR-SSCP method followed by sequencing in order to assess the genetic variability of coding and noncoding parts of the genome of Echinococcus granulosus (Cestoda ; Taeniidae) and to test whether or not the parasite populations are mainly self-fertilizing. For this, we analysed a sample of 110 E. granulosus metacestode isolates collected from different geographical regions (Southern Brazil, Europe and Australia) and from different intermediate hosts (ovine, bovine, human, macropod, swine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 17 publications
6
52
2
Order By: Relevance
“…The present study demonstrates that PCR-linked SSCP provides a method to display variation between E. granulosus strains, which has significant implications for studying the population genetics of this parasite and for epidemiology and disease control. As it was previously described by Haag et al (1999) in sheep strain, the most polymorphic loci found were Ag4 with four alleles, followed by Ag6 with three alleles. The dromedary prevalence of hydatidosis in Tunisia is low (6,5 %: Lahmar et al, 2004) by the absence of alleles A2 and A3, and the presence of the A4 (Ag4 gene), also found by Kamenetzky et al (2002), and classical C1 (CO1 gene) alleles.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The present study demonstrates that PCR-linked SSCP provides a method to display variation between E. granulosus strains, which has significant implications for studying the population genetics of this parasite and for epidemiology and disease control. As it was previously described by Haag et al (1999) in sheep strain, the most polymorphic loci found were Ag4 with four alleles, followed by Ag6 with three alleles. The dromedary prevalence of hydatidosis in Tunisia is low (6,5 %: Lahmar et al, 2004) by the absence of alleles A2 and A3, and the presence of the A4 (Ag4 gene), also found by Kamenetzky et al (2002), and classical C1 (CO1 gene) alleles.…”
Section: Discussionsupporting
confidence: 72%
“…T o date, few studies using PCR-SSCP approaches in E. granulosus were carried out (Haag et al, 1998;Haag et al, 1999;Zhang et al,1999;Kamenetzky et al, 2002) S D vantage to be extremely sensitive to the temperature variations and to be very largely dependent on the size of fragments of DNA (between 100 and 500 bp) (Kain et al, 1996;Zhang et al,1999;Martins-Lopes et al, 2001). The present study demonstrates that PCR-linked SSCP provides a method to display variation between E. granulosus strains, which has significant implications for studying the population genetics of this parasite and for epidemiology and disease control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations